Water Resource for Economic Development in Vietnam and Implications for Developing Countries (Global Journal of Management and Business Research, 2016)
In the framework of the project "Water Resource for Economic Growth and Sustainable Development: Theories and African and Middle East Experiences"
Keywords: water resource; water supply; water demand; water usage; loss from water; vietnam; middle east